Digital Marketing Strategies in Islamic Business: Future Trends, Challenges, and Research Directions - Afdhol Rinaldi; Machasin (MUI Kota Pekanbaru, 2026)
The rapid development of information technology has changed conventional trading patterns into online transactions through various digital platforms. This article aims to comprehensively examine digital marketing practices in the context of Islamic business, including current trends, challenges faced, and future research directions. The method used is a literature review with a descriptive-analytical approach to various relevant scientific articles from academic databases. The results of the study show that sharia-based digital marketing has great potential in the development of the Islamic economy, with the application of principles such as honesty (siddiq), trust, intelligence (fathonah), and good communication (tabligh). The main challenges identified include the limitations of digital literacy, the lack of halal product filters on e-commerce platforms, and the lack of fiqh muamalah education. The solutions offered include the development of sharia-based e-commerce platforms, Islamic digital training for business actors, and the integration of halal certification with digital marketing strategies. This research contributes to the development of Islamic digital marketing literature by providing a conceptual framework that integrates digital marketing practices with sharia economic values.